2004
DOI: 10.1016/j.jmb.2004.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Coat Protein in Pf1 Bacteriophage Determined by Solid-state NMR Spectroscopy

Abstract: The atomic resolution structure of Pf1 coat protein determined by solidstate NMR spectroscopy of magnetically aligned filamentous bacteriophage particles in solution is compared to the structures previously determined by X-ray fiber and neutron diffraction, the structure of its membrane-bound form, and the structure of fd coat protein. These structural comparisons provide insights into several biological properties, differences between class I and class II filamentous bacteriophages, and the assembly process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
134
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(146 citation statements)
references
References 37 publications
9
134
3
Order By: Relevance
“…Measurements were made of site-specific, solid-state NMR order parameters, ͗S͘, the values which are dimensionless quantities between 0 (mobile) and 1 (static) that characterize the amplitudes of molecular bond angular motions that are faster than microseconds. It was found that the protein subunit backbone is very static, and of particular interest, it appears to be static at residues glycine 15 and glutamine 16 where it had been previously thought to be mobile. In contrast to the backbone, several side chains display large-amplitude angular motions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements were made of site-specific, solid-state NMR order parameters, ͗S͘, the values which are dimensionless quantities between 0 (mobile) and 1 (static) that characterize the amplitudes of molecular bond angular motions that are faster than microseconds. It was found that the protein subunit backbone is very static, and of particular interest, it appears to be static at residues glycine 15 and glutamine 16 where it had been previously thought to be mobile. In contrast to the backbone, several side chains display large-amplitude angular motions.…”
mentioning
confidence: 99%
“…A variety of spectroscopic and diffraction studies of Pf1 have been carried out (5-19), including studies by solid-state NMR of the protein in the intact virion (16)(17)(18)(19), as in the present study, and by solution NMR of the isolated protein in detergent micelles (8,14) as a model of its structure in the membrane before virion assembly. Virion assembly occurs at the membrane in such a way that major coat protein subunits are packed in the filament as ␣-helices with their Nterminal regions on the outside and their C-terminal regions buried in the interior to interact with the DNA.One of the studies of the Pf1 virion by solid-state NMR was on magnetically aligned hydrated virions, and it characterized the path and orientation of the backbone of the ␣-helical major capsid protein subunit by means of 1 H-15 N polarization inversion spin exchange at the magic angle (PISEMA) (16,17). It was proposed that the subunit consists of an N terminus that forms a double hook, a C terminus with an unraveled ␣-helix, and a central portion of three ␣-helices with two bends near the center.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 was obtained from the structural form of the Pf1 coat protein in magnetically aligned bacteriophage particles [27]. In this sample, the protein is randomly labeled with ~20% 13 C and ~100% uniformly labeled with N. For economy of presentation, the portion of the C NMR spectrum between 80 and 160 ppm that does not contain signal intensity is not shown.…”
Section: Pisemamentioning
confidence: 99%
“…The single crystal of 13 C α , 15 N NAL was prepared by slow evaporation of aqueous solution after acetylating 13 C α and 15 N labeled leucine (Cambridge Isotope Laboratories, Andover, MA). Bacteriophage Pf1 was prepared as described previously [27]. Uniformly ~20% C and ~100% 15 N labeled bacteriophage was prepared using growth media obtained from Cambridge Isotope Laboratories, Inc. and selectively (Val, Leu, and Ile) 13 C α and 15 N labeled Pf1 was prepared using SLS media to avoid isotopic scrambling [31].…”
Section: Samplesmentioning
confidence: 99%